(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Component-based software development has grown rapidly as an approach that for rapid development of system by only using few resources and person-effort. The idea of popularity of component was its reuse and reducing the development costs and it can be achieved if the components offer reliable services and working raw lay architecture is available. Thus, integration of compatible components and their testing become an important part in CBSE and is the understanding of communication, dependency and coordination between the components. Component developers have to provide the detailed information about the component in the form of data sheet but in contrast of this the users of component are not satisfied with information available components. As a result of this, understanding data flow while integrating these components was a challenge. Component-based software as result is the development of complex systems by allowing integration of reusable and simple components. In-house testing of these components was a challenging area of research. There has always been a trouble in integrating the components and getting the optimized reliability as mentioned in the data sheet by the vendor. This in turn affects the quality and reliability of the software. Their research aims at finding the existing component selection, characteristics, repository of components, testing and challenges in science of CBSE. The systematic literature survey was based on 51 international journals collected from multiple-stage selection process. Keywords: component; component based software engineering; component developer; reliability; quality; repository